2010
DOI: 10.1007/s11999-009-1160-8
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Subvastus Approach: Improving the Results of Total Knee Arthroplasty: A Prospective, Randomized Trial

Abstract: Background Minimally invasive knee arthroplasty seeks to diminish the problems of traditional extensile exposures aiming for more rapid rehabilitation of patients after surgery. Questions/purposesTo determine if the subvastus approach results in less perioperative pain and blood loss, shorter hospital stay, and improved function at both early and long-term followup.Methods One hundred patients were enrolled in a prospective, randomized trial. Fifty were operated on using a minimally invasive subvastus approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
84
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(89 citation statements)
references
References 21 publications
2
84
0
3
Order By: Relevance
“…Although pioneers of this technique have reported excellent results, the longest mean follow up of a randomised control trial (RCT) in the literature is 36 months; clearly longer term results are awaited [38]. Much contemporary data come from health care systems where less invasive operative techniques may have been carried out on self-selecting, private patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although pioneers of this technique have reported excellent results, the longest mean follow up of a randomised control trial (RCT) in the literature is 36 months; clearly longer term results are awaited [38]. Much contemporary data come from health care systems where less invasive operative techniques may have been carried out on self-selecting, private patients.…”
Section: Discussionmentioning
confidence: 99%
“…One study defined MIS TKA as an approach that was less damaging to the extensor mechanism and avoided eversion of the patella [20]. Several MIS TKA techniques have been described: traditional mini (mini-medial parapatellar [15], mini-midvastus [20,21], mini-subvastus [22,43]) and fully innovative techniques (quad-sparing) [25,39,48]. Advocates of MIS TKA commonly suggest it allows patients faster recovery time [9,15], less blood loss [20], decreased soft tissue trauma [30,37], more pain relief [18], better cosmetic appearance [15,18,26], and measurable improvement of function [9,15,48].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to these positive findings, some recently published and well-designed studies [12][13][14][15][16] and 2 meta-analyses 17,18 have indicated that minimally invasive total knee arthroplasty could also have important shortcomings, such as prolonged operative time, an increased number of wound complications, and more malpositioning of the prosthesis. However, these randomized clinical trials had relatively short-term follow-up and had neither patient-reported outcomes nor radiographic evaluations.…”
mentioning
confidence: 99%